Dieta e dispersão de sementes por lycalopex vetulus (LUND, 1842) em áreas de cerrado stricto sensu do município de Chapada Dos Guimarães, Mato Grosso, Brasil - Cisneiro, Aimée Cruz (2020)
With an endemic distribution of the Cerrado, the hoary fox (Lycalopex vetulus) is a small canid considered vulnerable to extinction by the last Brazilian list of threatened mammals. Their diet is based on the consumption of insects and a considerable portion of fruits and small vertebrates, which indicates that the hoary fox can act as a seed disperser in this biome. Through the active search and field collection of fecal samples of L. vetulus, these samples were selected and analyzed, enabling the identification of the food items consumed, besides their frequency of occurrence and biomass. Invertebrates (66%) and wild fruits (65%) composed most of the diet, and small vertebrates (24%) were uncommon. A high frequency of termites (Isoptera; present in 60% of the feces) showed that this item represents great importance in the species' diet. For dispersion analyzes, were performed germination and viability tests on the seeds found in the feces, which pointed out that most of the tested species have a viability rate greater than 50%, while only five species germinated. The diet of the hoary fox was similar in composition to a study carried out in the same area 20 years ago. Moreover, L. vetulus could be considered a potential seed disperser since most of the plant species propagules found in their feces proved to be viable even after passing through their digestive tract.